2014
DOI: 10.1177/0021998314525065
|View full text |Cite
|
Sign up to set email alerts
|

Coupling pattern and efficacy of organofunctional silanes in wood flour-filled polypropylene or polyethylene composites

Abstract: The coupling efficacies of four silanes, i.e. n-propyl-trimethoxysilane, g-amino-propyltrimethoxysilane, g-methacryloxypropyl trimethoxy silane, and allyltrimethoxysilane, were investigated in wood flour-filled polypropylene or polyethylene composites. Compared to untreated composites, treatment of wood flour with these silanes alone did not cause any improvement in the mechanical strength of the ensuing composites. In the presence of dicumyl peroxide, composites treated with g-methacryloxypropyl trimethoxy si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Using of several additives and various formulation and/or processing attempts have been extensively studied so far to increase interfacial adhesion between components of WPCs. 315 Maleic anhydride grafted polyolefins (PE-g-MA, PP-g-MA, etc.) appear to be the most effective compatibilizers or coupling agents for WPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Using of several additives and various formulation and/or processing attempts have been extensively studied so far to increase interfacial adhesion between components of WPCs. 315 Maleic anhydride grafted polyolefins (PE-g-MA, PP-g-MA, etc.) appear to be the most effective compatibilizers or coupling agents for WPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has already been confirmed that various silanes can react with cellulose [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], lignin [ 33 , 34 , 35 , 36 , 37 , 38 ], and wood [ 39 , 40 , 41 , 42 , 43 ], and the results of our previous FT-IR analyses on waterlogged wood treated with organosilicons confirmed the formation of new chemical bonds between them [ 15 , 43 ], the details of the interactions and potential preferences of silanes to react with individual wood polymers remain not fully understood. Therefore, to unveil the mechanism of waterlogged wood stabilization by organosilicon compounds, further research is necessary that will help to better understand the wood–silane interactions, especially in highly decayed wood where the usual cellulose/lignin ratio and the regular chemical composition and structure of wood polymers are altered by degradation processes.…”
Section: Introductionmentioning
confidence: 99%